Missense variants in the X‐linked gene PRPS1 cause retinal degeneration in females. Issue 1 (17th October 2017) - Fiorentino, Alessia; Fujinami, Kaoru; Arno, Gavin; Robson, Anthony G.; Pontikos, Nikolas; Arasanz Armengol, Monica; Plagnol, Vincent; Hayashi, Takaaki; Iwata, Takeshi; Parker, Matthew; Fowler, Tom; Rendon, Augusto; et al.
Abstract: Retinal dystrophies are a heterogeneous group of disorders of visual function leading to partial or complete blindness. We report the genetic basis of an unusual retinal dystrophy in five families with affected females and no affected males. Heterozygous missense variants were identified in the X‐linked phosphoribosyl pyrophosphate synthetase 1 ( PRPS1 ) gene: c.47C > T, p.(Ser16Phe); c.586C > T, p.(Arg196Trp); c.641G > C, p.(Arg214Pro); and c.640C > T, p.(Arg214Trp). Missense variants in PRPS1 are usually associated with disease in male patients, including Arts syndrome, Charcot–Marie–Tooth, and nonsyndromic sensorineural deafness. In our study families, affected females manifested a retinal dystrophy with interocular asymmetry. Three unrelated females from these families had hearing loss leading to a diagnosis of Usher syndrome. Other neurological manifestations were also observed in three individuals. Our data highlight the unexpected X‐linked inheritance of retinal degeneration in females caused by variants in PRPS1 and suggest that tissue‐specific skewed X‐inactivation or variable levels of pyrophosphate synthetase‐1 deficiency are the underlying mechanism(s). We speculate that the absence of affected males in the study families suggests that some variants may be male embryonic lethal when inherited in the hemizygous state. The unbiased nature of next‐generation sequencing enables all possible modes of inheritance to be considered for association of gene variants with novel phenotypic presentation. Abstract : We report the genetic basis of an unusual retinal dystrophy with inter‐ocular asymmetry in families with only affected females. Heterozygous missense variants were identified in the X‐linked PRPS1 gene. PRPS1 missense variants are usually associated with disease in males, including Arts Syndrome and Charcot‐Marie‐Tooth. The unexpected X‐linked inheritance suggests tissue specific skewed X‐inactivation or variable levels of PRS‐I deficiency are the underlying mechanism(s). The absence of affected males in these families suggests that some PRPS1 variants may be male lethal.